A conductive analcime molecular sieve and its preparation method and application
By introducing lanthanide metal ions into the skeleton of zeolite molecular sieve to replace aluminum ions, the conductive zeolite molecular sieve is solved, and the conductivity improvement and application enhancement in the field of electrocatalytics is achieved.
Patent Information
- Application Number
- CN202411951540.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Due to the limitation of electrical insulation, the existing square zeolite molecular sieve has failed to effectively improve its intrinsic conductivity, resulting in insufficient application in the field of electrocatalysis.
By introducing lanthanide metal ions into the zeolite molecular sieve framework, replacing part of aluminum ions, forming a conductive zeolite molecular sieve, the chemical formula is NaSi2AlyR2-yO6•H2O, y=0.7-1.3, and R is a lanthanide metal.
The order of magnitude improvement of the conductivity of zeolite molecular sieve is achieved, giving it reactive activity and stability in electrochemical reactions, and is suitable for industrial applications.
Smart Images

Figure CN119370860B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of inorganic metal catalysts, and in particular relates to a conductive analcime molecular sieve and a preparation method and application thereof. Background Art
[0002] As an important type of zeolite molecular sieve material, analcime has the chemical formula NaSi2AlO6•H2O. Due to its advantages such as uniform pore structure, large specific surface area, high surface polarity and high thermal stability, it has been widely used in adsorption, ion exchange and traditional catalysis. However, analcime is limited in its application in the field of electrochemical energy conversion due to its own electrical insulation. Currently, catalytically active substances such as composite metal compounds are usually used in analcime to improve the conductivity of the overall catalytic system, rather than improving the intrinsic conductivity of analcime. Therefore, the reasonable improvement of the conductivity of analcime molecular sieve is the key to improving its practicality in the field of electrocatalysis.
[0003] At present, the main problem in the prior art is that the intrinsic conductivity of the analcime molecular sieve is not improved by modification with the addition of external substances, and it has not been found that the modified analcime molecular sieve itself can improve its conductivity. Summary of the invention
[0004] The present application discloses a conductive analcime molecular sieve and a preparation method and application thereof, aiming to solve the technical problem of poor intrinsic conductivity of the existing analcime molecular sieve.
[0005] In order to achieve the above purpose, the technical solution of this application is:
[0006] The first aspect of the present application provides a conductive analcime molecular sieve, the chemical formula of which is NaSi2Al y R 2-y O6•H2O;
[0007] Wherein, y=0.7-1.3; R is selected from one of the lanthanide metals.
[0008] In combination with the first aspect, preferably, its chemical formula is NaSi2Al y R 2-y O6•H2O;
[0009] Among them, y=0.7-1.3; R is selected from one of lanthanum ion, samarium ion and neodymium ion.
[0010] The second aspect of the present application provides a method for preparing the conductive analcime molecular sieve described in the first aspect, the preparation method comprising:
[0011] The metal source, aluminum isopropoxide, colloidal SiO2, NaOH and water are mixed and stirred, and then subjected to hydrothermal treatment, separated and collected, and then ground to obtain the conductive analcime molecular sieve;
[0012] The metal source is a lanthanide metal compound.
[0013] In combination with the second aspect, preferably, the metal source is one of lanthanum nitrate, samarium nitrate and neodymium nitrate.
[0014] In combination with the second aspect, preferably, the metal source, aluminum isopropoxide, colloidal SiO2, NaOH and water are added in a molar ratio of 0.2-0.5:2:15:20:300.
[0015] In combination with the second aspect, preferably, the molar ratio of the metal source, aluminum isopropoxide, colloidal SiO2, NaOH and water added is 0.3-0.4:2:15:20:300.
[0016] In combination with the second aspect, preferably, the temperature of the hydrothermal treatment is 140-190°C.
[0017] In combination with the second aspect, preferably, the hydrothermal treatment is performed for 20-30 h.
[0018] The third aspect of the present application provides the use of the conductive analcime molecular sieve described in the first aspect or the conductive analcime molecular sieve prepared by the preparation method described in the second aspect in an electrocatalytic reaction.
[0019] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0020] The conductive analcime molecular sieve provided by the present application not only retains the pore advantages of the intrinsic morphology and structure of the analcime molecular sieve by introducing lanthanide metals into the analcime molecular sieve framework to replace part of the aluminum ions, but also the atomic radius of the lanthanide metal ions is larger than that of the aluminum ions, which can expand the pore size and retain its excellent specific surface area, and can also achieve polarization of the analcime molecular sieve framework, reduce the band gap width while promoting the transfer of electrons, achieve an order of magnitude increase in conductivity, and thus give it reaction activity and stability in electrochemical reactions, making it suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 Scanning electron microscope images of La-conductive analcime molecular sieve and B1-analcime molecular sieve provided in the examples of the present application;
[0023] Among them, (a) B1-analcimite molecular sieve; (b) La-conductive analcime molecular sieve; scale bar: 2 μm;
[0024] Figure 2 XRD comparison diagram of La-conductive analcime molecular sieve and B1-analcime molecular sieve provided in the examples of the present application;
[0025] Figure 3 This is a partial enlarged comparison diagram of XRD of La-conductive analcime molecular sieve and B1-analcime molecular sieve provided in the examples of the present application;
[0026] Figure 4 This is an EDS image of the B1-analcite molecular sieve provided in the examples of the present application;
[0027] Figure 5 Element distribution diagram of La-conductive analcime molecular sieve provided in the examples of the present application;
[0028] Figure 6 A linear sweep voltammetric curve of a catalyst made of conductive analcime molecular sieve provided in an embodiment of the present application in electrocatalytic CO2 reduction;
[0029] Figure 7 This is a product distribution diagram of the catalyst made of conductive analcime molecular sieve provided in the examples of the present application in the electrocatalytic CO2 reduction. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0031] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0032] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0033] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0034] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0035] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0036] In the first aspect, the present invention provides a conductive analcime molecular sieve, the chemical formula of which is NaSi2Al y R 2- y O6•H2O;
[0037] Wherein, y=0.7-1.3; R is selected from one of the lanthanide metals.
[0038] Among them, not only can the pore advantages of the intrinsic morphology of the analcime molecular sieve be retained, but the atomic radius of the lanthanide metal ions is larger than that of the aluminum ions, which can expand the pore size and retain the excellent specific surface area. It can also achieve polarization of the analcime molecular sieve framework, reduce the band gap width, and promote the transfer of electrons, thereby achieving an order of magnitude increase in conductivity, thereby giving it reaction activity and stability in electrochemical reactions, making it suitable for industrial applications.
[0039] It should be noted that R is preferably one of the lanthanide metals, more preferably one of lanthanum ions, samarium ions, and neodymium ions. Among them, since these metal ions have the characteristics of high charge, large ionic radius, strong self-polarization ability, etc., they can be introduced into the analcime molecular sieve framework, replace part of the aluminum ions in the analcime molecular sieve, increase the specific surface area, polarize the framework, reduce the bandgap width, promote electron transmission, and thus improve the conductivity of the conductive analcime molecular sieve, achieving an order of magnitude improvement in conductivity.
[0040] In a second aspect, the present application also provides a method for preparing the conductive analcime molecular sieve described in the first aspect, the preparation method comprising:
[0041] The metal source, aluminum isopropoxide, colloidal SiO2, NaOH and water are mixed and stirred, and then subjected to hydrothermal treatment, separated and collected, and then ground to obtain the conductive analcime molecular sieve;
[0042] The metal source is a lanthanide metal compound.
[0043] It should be noted that the water used in the present application is preferably deionized water, which can eliminate the influence of other impurities on the reaction.
[0044] It should be noted that the present application is subjected to grinding treatment after hydrothermal treatment: 1) the lanthanide elements are evenly distributed in the structure, which is beneficial for the embedding of lanthanide metal ions into the molecular sieve framework; 2) the particles of the modified analcime powder are made uniform, the grain size is reduced, which is beneficial for the transmission of electrons, thereby improving the conductivity; 3) for the application of modified analcime as a carrier, sufficient grinding will reduce the size of the modified analcime powder, which is beneficial for the uniform and highly dispersed loading of metal catalysts, so that the metal catalysts show higher activity.
[0045] In the embodiment of the present application, the metal source is preferably one of lanthanum nitrate, samarium nitrate and neodymium nitrate. Among them, by selecting the nitrate corresponding to these metal ions, it is not only possible to prevent the influence of other acid radicals, but also to be uniformly dissolved in the reaction solution, providing a basis for further sufficient reaction.
[0046] In the embodiment of the present application, the molar ratio of adding the metal source, aluminum isopropoxide, colloidal SiO2, NaOH and water is preferably 0.2-0.5:2:15:20:300, more preferably 0.3-0.4:2:15:20:300, such as 0.3:2:15:20:300, 0.35:2:15:20:300, 0.4:2:15:20:300 or any ratio within the ratio range. Among them, by controlling the ratio of each substance added, the amount of metal ions introduced can be regulated, and it can be ensured that each substance in the solution is fully contacted, thereby controlling the number of metal ions in the metal source entering the framework of the analcime molecular sieve, thereby improving the conductivity of the conductive analcime molecular sieve. And it is possible to achieve an increase in the order of magnitude of conductivity, thereby improving the application in electrocatalytic reactions.
[0047] In the embodiment of the present application, the temperature of the hydrothermal treatment is preferably 140-190 ° C, for example, 140 ° C, 150 ° C, 160 ° C, 170 ° C, 180 ° C, 190 ° C or any temperature within the range; the time is preferably 20-30 h, for example, 20 h, 22 h, 24 h, 26 h, 28 h, 30 h or any time within the range. Among them, by controlling the temperature and time of the hydrothermal treatment, the structure and morphology of the crystal can be regulated, the metal ions are introduced into the framework of the analcime molecular sieve, and the integrity of the crystallization process can be guaranteed.
[0048] In the third aspect, the embodiment of the present application also provides the use of the conductive analcime molecular sieve described in the first aspect or the conductive analcime molecular sieve prepared by the preparation method described in the second aspect in an electrocatalytic reaction. The conductive analcime molecular sieve prepared based on the above-mentioned preparation maintains the pore advantages of the original analcime molecular sieve, achieves an order of magnitude improvement in conductivity, and then gives it the reaction activity and stability in the electrochemical reaction, which is suitable for industrial application. The electrocatalytic reaction includes electrocatalytic CO2 reduction reaction, water electrolysis, fuel cell and nitrogen reduction reaction.
[0049] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0050] Example 1
[0051] This embodiment provides a method for preparing La-conductive analcime molecular sieve, which specifically comprises:
[0052] La(NO3)3•6H2O, C9H 21AlO3, NaOH, colloidal SiO2 and deionized water were mixed in a molar ratio of 0.4:2:20:15:300, magnetically stirred at room temperature for 12 h, and hydrothermally reacted at 180 °C for 24 h. The obtained solid was then centrifuged, washed three times with deionized water, and transferred to a vacuum oven and dried at 60 °C for 5 h. Finally, the dried sample was ground to obtain La-conductive analcime molecular sieve.
[0053] Example 2
[0054] This embodiment provides a method for preparing Sm-conductive analcime molecular sieve, which specifically comprises:
[0055] Sm(NO3)3•6H2O, C9H 21 AlO3, NaOH, colloidal SiO2 and deionized water were mixed in a molar ratio of 0.3:2:20:15:300, magnetically stirred at room temperature for 15 h, and hydrothermally reacted at 150 ℃ for 20 h. The obtained solid was then centrifuged, washed three times with deionized water, and transferred to a vacuum oven and dried at 60 ℃ for 5 h. Finally, the dried sample was ground to obtain Sm-conductive analcime molecular sieve.
[0056] Example 3
[0057] This embodiment provides a method for preparing Nd-conductive analcime molecular sieve, which specifically comprises:
[0058] Nd(NO3)3•6H2O, C9H 21 AlO3, NaOH, colloidal SiO2 and deionized water were mixed in a molar ratio of 0.35:2:20:15:300, magnetically stirred at room temperature for 10 h, and hydrothermally reacted at 170 °C for 20 h. The obtained solid was then centrifuged, washed three times with deionized water, and transferred to a vacuum oven and dried at 60 °C for 5 h. Finally, the dried sample was ground to obtain Nd-conductive analcime molecular sieve.
[0059] At the same time, in order to verify the comprehensive performance of the conductive analcime molecular sieve prepared in the above examples, the present application provides the following comparative examples for detailed description.
[0060] Comparative Example 1
[0061] In this comparative example, the analcime molecular sieve without any modification in Example 1 is used as comparative example 1, and is recorded as B1-analcimite molecular sieve.
[0062] In order to verify the appearance structure of the conductive analcime molecular sieve prepared in the examples of the present application, scanning electron microscopy and XRD tests were performed on the La-conductive analcime molecular sieve prepared in the examples of the present application. The test results are as follows: Figure 1-2 As shown. Among them, Figure 1The scanning electron microscope images of La-conductive analcime molecular sieve and B1-analcime molecular sieve; Figure 2 XRD patterns of La-conductive analcime molecular sieve and B1-analcime molecular sieve.
[0063] according to Figure 1 As we know, Figure 1 (a) It can be seen that the B1-analcimite molecular sieve is a polyhedron, which is similar to a micron sphere. (b) The morphology of the modified La-conductive analcime molecular sieve has not changed.
[0064] according to Figure 2 As we know, the characteristic peak position of the conductive analcime molecular sieve modified by La has not changed significantly, but it can be clearly found by comparison that the XRD peak has moved to a low angle. This is because the lattice volume of La atoms is larger than that of Al atoms. After La atoms replace Al atoms in the zeolite molecular sieve, the XRD spectrum shifts to the low angle direction.
[0065] In order to verify the degree of substitution of the conductive analcime molecular sieve prepared in the examples of the present application, an EDS test was performed on the La-conductive analcime molecular sieve prepared in the examples of the present application. The test results are as follows: Figure 3-Figure 4 As shown. Among them, Figure 3 This is the EDS image of B1-analcime molecular sieve; Figure 4 This is the element distribution diagram of La-conductive analcime molecular sieve.
[0066] according to Figure 3 As we know, the Al, Na, O, and Si elements in the B1-analcime molecular sieve are evenly distributed in the analcime molecular sieve. Figure 4 As known, the Al, Na, O, and Si elements in the La-conductive analcime molecular sieve are also evenly distributed, and a small amount of La element is also evenly distributed in the conductive analcime molecular sieve, indicating that La ions are successfully introduced into the conductive analcime molecular sieve framework. Among them, the element content test results of B1-analime molecular sieve are shown in Table 1, and the element content test results of La-conductive analcime molecular sieve are shown in Table 2:
[0067] Table 1 Test results of element content of B1-analcime molecular sieve
[0068]
[0069] Table 2 Test results of element content of La-conductive analcime molecular sieve
[0070]
[0071] According to the test results in Table 1 and Table 2, it can be clearly seen that La ions are doped into the analcime molecular sieve and replace part of the aluminum ions.
[0072] In order to verify the specific surface area and conductivity of the conductive analcime molecular sieve prepared in the examples of the present application, the La-conductive analcime molecular sieve, Sm-conductive analcime molecular sieve, Nd-conductive analcime molecular sieve prepared in the examples of the present application and the B1-analime molecular sieve prepared in the comparative example were tested for conductivity using a powder conductivity tester; the specific surface area test was performed using a fully automatic specific surface area and pore size analyzer; the results are shown in Table 3.
[0073] Table 3 Specific surface area and conductivity test results of analcime molecular sieve prepared in Example
[0074]
[0075] According to Table 3, compared with the specific surface area of the unmodified analcime molecular sieve, the specific surface areas of the modified La-conductive analcime molecular sieve, Sm-conductive analcime molecular sieve, and Nd-conductive analcime molecular sieve have basically not decreased, indicating that the original three-dimensional pore structure of the analcime molecular sieve is well preserved.
[0076] Compared with the conductivity of the unmodified analcime molecular sieve, the conductivity of the modified La-conductive analcime molecular sieve is 0.213 S / m, the conductivity of the Sm-conductive analcime molecular sieve is 0.167 S / m, and the conductivity of the Nd-conductive analcime molecular sieve is 0.209 S / m. The conductivity of the La-conductive analcime molecular sieve, the Sm-conductive analcime molecular sieve, and the Nd-conductive analcime molecular sieve prepared in the embodiment is greatly improved by an order of magnitude, showing excellent conductive properties. By adopting the same preparation process, the lanthanide metal is introduced into the analcime molecular sieve framework, which can also achieve an improvement in conductivity. The improvement in conductivity greatly improves the practicability of the analcime molecular sieve material in the fields of energy conversion and catalysis.
[0077] In order to verify the application of the conductive analcime molecular sieve prepared in the example of the present application in the electrocatalytic reduction of CO2: a catalyst was prepared using modified analcime as a carrier and CuO as an active component to carry out electrocatalytic reduction of CO2.
[0078] The preparation method of the catalyst is as follows: weigh 85.6 mg of CuSO4•5H2O powder, add 300 microliters of deionized water, and ultrasonicate for 2-5 min to ensure that the solute is evenly dispersed and there is no precipitate; weigh 200 mg of conductive zeolite molecular sieve into a glass bottle, use a pipette to add the above CuSO4 solution in batches, and ultrasonicate the mixed solution for 2 h to allow CuSO4 to fully infiltrate the modified molecular sieve. The sonicated solution is vacuum dried at 80 °C for 2 h to remove moisture, and then transferred to a tubular furnace and annealed at 300 °C for 2 h under Ar gas protection atmosphere to obtain the catalyst.
[0079] Test method: Use flow cell to test CO2 reduction performance: add 20 mg of catalyst to isopropanol and nafion solution and mix evenly, then spray the mixed solution on 1 3 cm 2 The flow rate of CO2 is fixed at 30 SCCM by a mass flow controller. Carbon paper is used as the working electrode, Pt sheet is used as the counter electrode, Hg / HgO electrode is used as the reference electrode, the electrolyte is 1M KOH solution, the cathode and anode are separated by an anion exchange membrane, and the gas phase product is quantitatively analyzed by gas chromatography. The test results are shown in Figure 6-7 As shown:
[0080] according to Figure 6 It can be seen that the LSV curve (linear sweep voltammetry curve) of the catalyst in the electrocatalytic CO2 reduction shows that the catalyst transition point is near -0.3 V, and the current density can reach 800 mA / cm at a voltage of -2.0 V. 2 , indicating that the catalyst has higher reactivity and faster reaction rate.
[0081] according to Figure 7 It can be seen that the product distribution diagram of the catalyst in the electrocatalytic CO2 reduction shows that the products are composed of ethane, ethylene, methane, CO and H2. At a low potential of -1.0 V, the Faraday efficiency of ethylene reaches 59%, the Faraday efficiency of C2 products is close to 65%, and the yield of H2 is only 10%, indicating that the modified analcime loaded with CuO is beneficial to the formation of C2 products and has an excellent inhibitory effect on the competitive hydrogen evolution reaction.
[0082] Therefore, the conductive analcime molecular sieve provided by the present application can not only retain the pore advantages of the intrinsic morphology and structure of the analcime molecular sieve by introducing lanthanide metals into the analcime molecular sieve framework to replace part of the aluminum ions, but also the atomic radius of the lanthanide metal ions is larger than that of the aluminum ions, which can expand the pore size and increase its specific surface area. It can also realize the polarization of the zeolite molecular sieve framework, reduce the band gap width, promote the transfer of electrons, and achieve an order of magnitude increase in conductivity, thereby giving it reaction activity and stability in electrochemical reactions, making it suitable for industrial applications.
[0083] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0084] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. Application of La-conductive analcime molecular sieve in electrocatalytic reaction, characterized in that: The electrocatalytic reaction is an electrocatalytic CO2 reduction reaction; The preparation method of the La-conductive analcime molecular sieve comprises: La(NO3)3·6H2O, C9H 21 AlO3, NaOH, colloidal SiO2, and deionized water were mixed in a molar ratio of 0.4:2:20:15:300, magnetically stirred at room temperature for 12 h, and hydrothermally reacted at 180 °C for 24 h. The resulting solid was then centrifuged, washed with deionized water three times, and then transferred to a vacuum oven and dried at 60 °C for 5 h. Finally, the dried sample was ground to obtain La-conductive analcime molecular sieve. In the electrocatalytic CO2 reduction reaction: La-conductive analcime molecular sieve is used as a carrier and CuO is used as an active component to prepare a catalyst for electrocatalytic CO2 reduction.
Citation Information
Patent Citations
Solid electrolyte material and preparation method and application thereof
CN117438641A